Field reports form for submitting seasonal observations of Iowa birds, Beth Proescholdt, fall 1988 - Proescholdt, Bethet al (1988)
List of birds and locations contributed by Beth Proescholdt. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed